POTENTIAL MARKETING EFFORTS OF TOURISMIN LUMBUNG VILLAGE BALI - Ni Putu Dyah Krismawintari; IWK Tejakusuma; Ni Luh Putu Suarmi Sri Patni (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
Sustainable tourism development leads to the use of natural and human resources for the long term. The success of the economic development of a region requires cooperation between the community and the government in utilizing existing resources. The island of Bali is known for its various tourism potentials consisting of natural and cultural tourism. There is one area in Tabanan Regency to be precise in Lumbung Village which has several tourism and cultural potentials but is not yet known and developed. The importance of optimizing the potential of an area is one of the efforts to improve the welfare of the community and to preserve its customs and culture. Marketing efforts of a region require the role of various parties and receive government support. This is expected to build community-based sustainable tourism. This social humanities research is explorative-qualitative in nature with the findings being reduced and analyzed using a marketing mix consisting of Product,Price, Place, Promotion, Physical Evidence, People and Process and analyzing 4A of tourist destinations ( attraction, access, facilities /amenities, and supporting institutions /ancillary. Data retrieval through indepth interviews with current village leaders and the Head of Community Empowerment Institutions to obtain information about the efforts that havebeen made in marketing tourism potential in Lumbung Village. Research results Marketing efforts for Lumbung Village tourism potential by taking into account the elements of the mix marketing and the principles of socio-cultural, environmental and economic tourism. Principles of sustainable tourism in Lumbung Village: preserving traditional values while maintaining culture, biodiversity, maintaining the beauty of the rural atmosphere, and improving the community's economy. Keywords: Marketing Mix, Tourism potential, Sustainable tourism